Monitoring System for Electrical Energy Use and Charging Electricity Tokens Based on Website and Whatsapp Application - Novri Amsyah; Asmar Asmar; Rudy Kurniawan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
The large number of equipment or electrical loads used causes large amounts of electrical energy usage. To determine the amount of electrical energy used, you can install an electrical energy meter whose results can be monitored via an LCD display. In this research, a website-based application was designed that can monitor electrical energy usage, by providing information in the form of voltage, current, power, and active power usage over time. Apart from that, this website can also top up electricity tokens as a feature to limit the use of electrical energy that will be used by users and is equipped with a notification message for remaining electricity tokens to the Whatsapp application. This system was developed using an ESP32 microcontroller which will provide data, process data, and present data from instrument measurements, then send the measurement results data every 15 seconds to the monitoring website. From the test results, the tool can measure electrical quantities such as current and voltage. The tool can also send measurement results to the website and store measurement data in a database. Test results for sending notification messages, the message was successfully sent to WhatsApp media if the electricity token met the specified conditions.